Peningkatan Daya Saing Usaha Melalui Pengembangan Produk Olahan Pada UMKM Kopi Danci - Nugraha, Alifian; Nurhasanah, Siti; Hasanah, Siti Uswatun; Rhofiah, Bela Maulidahtul (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
The Danci Coffee UMKM, which was established in 2018 in Danci Hamlet, Kemiri Village, Jember Regency, faces challenges in increasing the added value and competitiveness of its products. Although it has its own coffee plantation and markets its products abroad, this UMKM only produces coffee beans and coffee powder, without diversifying processed products that can open up new market opportunities. This community service activity aims to develop processed coffee products in the form of coffee opak, with the aim of increasing the knowledge and skills of UMKM actors in innovative coffee processing techniques and effective marketing strategies. Community service methods include observation, socialization, product development training, and monitoring and evaluation. The results of this activity show that training and development of processed coffee products can improve the ability of UMKM actors to produce more valuable and competitive products. In conclusion, the development of processed products such as coffee opak not only increases product variety but also expands the market and improves the welfare of the local community. These results show the importance of product innovation in supporting poverty and the growth of UMKM in the agricultural sector, especially coffee.